“Cardos” of two worlds: Transfer and re-signification of the uses of thistles between the Iberian Peninsula and Argentina - Hernández Bermejo, J. Esteban (2019)
“Thistles” constitute a group of prickly herbaceous plants included in the Cardueae tribe (Asteraceae), but in the popular sense that concept is frequently applied to other species of the same family, as well as to some Dipsacaceae, Bromeliaceae, Apiaceae or Cactaceae. Since antiquity, the cultivation and use of thistles for food and medicinal purposes has been well known in the Mediterranean cultures. The different popular knowledge could allow us to refer to a “thistle culture”. During the exploration of America, many of those species and their associated knowledge were transferred from the Old to the New World. In Argentina, several species of thistles, especially Cynara cardunculus, spread extensively throughout the pampas. From early times, they constituted a source of food and low quality fuel, and in several cases they were also employed in popular medicine, with diverse uses, some of which are still in practice. The local importance of some species is mentioned in gaucho literature, arts, and gastronomy. In the 20th century, a large production of artichokes from introduced crops that increased local agro-diversity was recorded in Argentina. This contribution summarizes some aspects of the transfer and re-signification of the thistle between the Iberian Peninsula and Argentina.